The Wiley handbook on the aging mind and brain - Rizzo, Matthew; Anderson, Steven W. (Wiley, 2018)
"Discusses brain functions and behavior across the lifespan, brain disease and dysfunction, optimizing brain function in health and disease, and legal and ethical issues"--